Correction: Mechanism and principle of doping: realizing of silver incorporation in CdS thin film via doping concentration effect. Issue 50 (11th November 2022) - Najm, A. S.; Aljuhani, Abdulwahab; Naeem, Hasanain Salah; Sopian, K.; Ismail, Raid A.; Holi, Araa Mebdir; Sabri, Laith S.; Abdullah AL-Zahrani, Asla; Rasheed, Rashed Taleb; Moria, Hazim
Abstract : Correction for 'Mechanism and principle of doping: realizing of silver incorporation in CdS thin film via doping concentration effect' by A. S. Najm et al., RSC Adv., 2022, 12, 29613–29626, ; https://doi.org/10.1039/D2RA04790J .